If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -0.5(-2) + 2 Multiply -0.5 * -2 y = 1 + 2 Combine like terms: 1 + 2 = 3 y = 3 Solving y = 3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 3
| Z+35=11 | | -y^2+7y-9=0 | | Z-26=-44 | | (x-5)(x^2-2x-7)= | | b*2+2b=0 | | x^3+3x^2-81x-243= | | 5u+14=-10u-2 | | 5u=10u-2 | | -0.01x^2+.7x+6.1= | | 8=(n)/(-7)-5 | | 3/4x-15=30 | | 3.6+10m=6.41 | | 0.5x+4=13.5 | | 6x+20=14-52 | | Y^2-9y+74=0 | | 120+18m=408 | | 34n-120=390 | | (3x/7y^3)^2 | | 5x=x+30(5) | | (2x^3y^3-3xy+4)(4xy^3)=z | | g(x)=x^2-12x+39 | | 6y-4y^2=-7 | | 10n+6=9 | | 4x^4-23x^2-6=0 | | 14x=108 | | 6x^4-23x^2-6=0 | | -11=8w-11 | | -46=5x-.333 | | 2x-36=26 | | -4x-4x=52-4 | | 25x-8x+2=0 | | n(n-3)=180 |